Talleres para fomentar el cuidado de la naturaleza para niños y niñas de educación inicial - Bastidas Espin, Doris Marianela (2022)
The purpose of this proposal is to promote values, in children from 3 to 5 years of Initial Education of the Pujilí Educational Unit, such as respect and care for nature, which are important for healthy coexistence and relationship of respect between this and the being human. Likewise, it allows to preserve a habitable world and acquire the learning skills and competences for the future; therefore, it is proposed to design workshops to promote the care of nature in children of Initial Education, through a constructivist approach with a qualitative methodological design, where the characteristics, qualities and interest of children are determined during the execution of the activities. The research will be field, which will allow obtaining validation data, through the application of the exploratory and descriptive technique. For this reason, the proposal consists of eight practical workshops based on orality such as: stories, rhymes, riddles, possessed and songs through which it is intended to raise awareness about caring for nature. For this, the validation was subjected to the analysis process by experts who have the fourth academic level, obtaining "Very Good" as a result, since they mention that the present and future generations of students of the Initial Education level and the teachers are the keys of the change. In addition, it will serve as a means of support in the teaching-learning process inside and outside the classroom.